Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1086/507337
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Post–Organ Transplantation Cytomegalovirus Disease with Ganciclovir: A Meta‐Analysis Comparing Prophylactic and Preemptive Therapies

Abstract: On the basis of indirect comparisons of meta-analyses of prevention strategies, universal prophylaxis and preemption are equally effective in reducing the incidence of CMV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 48 publications
3
96
0
Order By: Relevance
“…Reassuringly, clinical trials have demonstrated the efficacy of preemptive therapy in CMV disease prevention [54][55][56]59] . Three meta-analyses that collectively analyzed data from prospective clinical trials confirmed the efficacy and benefits of preemptive therapy in the prevention of CMV disease [34,35,62] . When conducted properly, preemptive therapy, with the use of oral ganciclovir, IV ganciclovir, or valganciclovir resulted in reduction of CMV disease by about 70% [34,35,62] .…”
Section: Preemptive Therapymentioning
confidence: 91%
See 1 more Smart Citation
“…Reassuringly, clinical trials have demonstrated the efficacy of preemptive therapy in CMV disease prevention [54][55][56]59] . Three meta-analyses that collectively analyzed data from prospective clinical trials confirmed the efficacy and benefits of preemptive therapy in the prevention of CMV disease [34,35,62] . When conducted properly, preemptive therapy, with the use of oral ganciclovir, IV ganciclovir, or valganciclovir resulted in reduction of CMV disease by about 70% [34,35,62] .…”
Section: Preemptive Therapymentioning
confidence: 91%
“…CMV was a major cause of mortality after liver transplantation prior to the availability of intravenous (IV) and oral ganciclovir. Several recent meta-analyses have demonstrated that the use of anti-CMV drugs, either through antiviral prophylaxis or preemptive therapy, have led to significant reduction in the overall mortality after solid organ transplantation [19,[33][34][35] . However, despite much improvement in outcome, there is emerging data to suggest that even in the contemporary era, with widespread use of antiviral prophylaxis, development of delayed onset CMV disease remains a common problem, and importantly, is associated with significantly increased risk of mortality after liver transplantation [32] .…”
Section: Impact On Mortalitymentioning
confidence: 99%
“…Three metaanalyses that collecti vely analyzed data from prospective clinical trials demonstrated the benefits of preempti ve therapy in preventing CMV dis ease [35,36,68] . When conducted properly, preempti ve therapy, with the use of oral ganciclovir, IV ganciclovir, or val ganciclovir resulted in the reduction of CMV disease by about 70% [35,36,68] . Moreover, preemptive therapy is much less likely associated with late onset CMV disease (unlike in antiviral prophylaxis, as discussed below) [59,66] .…”
Section: Preemptive Therapymentioning
confidence: 99%
“…Anti viral prophylaxis is highly effecti ve in preventing the direct, as well as the indirect effects of CMV after li ver transplantation [4,5,35,36,68] . Compared to placebo or no treat ment, patients who received antiviral prophylaxis had lower incidence of CMV disease (58%80% reduction) and CMV infection (about 40% reduction) [68] .…”
Section: Antiviral Prophylaxismentioning
confidence: 99%
“…While prophylaxis has been associated with superior graft and patient survival [18,19], as well as cost and quality of life benefits [20] compared to a preemptive strategy, the latter may be appropriate for patients at risk for CMV disease with contraindications to oral valganciclovir therapy [17,21]. In such an approach, monitoring of the serum C-MV PCR is conducted at regular intervals (often weekly) to detect infections before tissue-invasive disease results [17].…”
Section: Discussionmentioning
confidence: 99%